2002
DOI: 10.1053/jlts.2002.35927
|View full text |Cite
|
Sign up to set email alerts
|

The new liver allocation system: Moving toward evidence-based transplantation policy

Abstract: In 1999, the Institute of Medicine suggested that instituting a continuous disease severity score that de-emphasizes waiting time could improve the allocation of cadaveric livers for transplantation. This report describes the development and initial implementation of this new plan. The goal was to develop a continuous disease severity scale that uses objective, readily available variables to predict mortality risk in patients with end-stage liver disease and reduce the emphasis on waiting time. Mechanisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
415
2
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 668 publications
(432 citation statements)
references
References 16 publications
8
415
2
7
Order By: Relevance
“…This flexibility would allow the system to be adjusted for a maximization of outcomes. 10 The MELD also allows for reproducible comparison of patients awaiting transplantation, as well as comparison of transplant recipients across geographic areas. From these data, it has become clear that there is disparity among transplant centers when it comes to the selection of patients for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…This flexibility would allow the system to be adjusted for a maximization of outcomes. 10 The MELD also allows for reproducible comparison of patients awaiting transplantation, as well as comparison of transplant recipients across geographic areas. From these data, it has become clear that there is disparity among transplant centers when it comes to the selection of patients for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, no multivariable analysis has been performed for bacterial infections. (27) Pre-OLT sarcopenia associated with mortality (p = 0.06) 1 Non-significant association of continued reduction in muscle area with higher mortality (p = 0.08) Only one study reported that five patients had confirmed acute graft rejection without specifying them as (non)sarcopenic (27).…”
Section: Posttransplantation Complications and Transplantation-relatementioning
confidence: 99%
“…The combination of waiting list mortality and posttransplantation survival are key deciding factors in waiting list placement. Currently, the Model for End-stage Liver Disease (MELD) score, a validated risk-based system that predicts waiting list mortality, is used to allocate donor livers (1). Although the introduction of the MELD score has led to a decreased number of patients on the waiting list, shortened waiting time, and decreased waiting list mortality despite increasing disease severity (2), objective parameters reflecting a patient's nutritional and functional status in particular are lacking and attempts have been made to modify and improve the MELD score (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, mortality risk in patients with AH can be predicted by various models, including the Model for End-Stage Liver Disease (MELD) score. [2][3][4][5][6][7] Hyponatremia is a sign of excessive vasopressin secretion and is predictive of poor survival in patients with cir- CONCLUSION: MELD and MELDNa were similar predictors of 180-day mortality; however, MELDNa was a better predictor of mortality than MELD in patients with ascites. Hyponatremia in patients with AH without ascites is not a predictor of mortality because it may have a dilutional basis secondary to excessive intake of low-osmolar alcohol.…”
Section: © 2011 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%